Sosialisasi Penggunaan Artificial Intelligence untuk Anak-Anak Komunitas Jendela Jakarta di Manggarai Utara - Izra Noor Zahara Aliya; Cendana Putri Aulia; Moh. Azzam Priyanto; Yanuar Hakam Rosyadi A; Dhian Satria Yudha Kartika (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This Community Service activity aims to socialize the use of Artificial Intelligence (AI) to children aged 6-13 years in the Window Community, Jakarta, North Manggarai Branch with an exciting and interactive approach. Through the topic "AI: A New Friend to Help Our Daily Activities," this activity aims to introduce AI technology which can later help children's daily activities and increase insight regarding current technological developments. The methods used include a pre-test to measure initial knowledge, delivery of material about AI and machine learning, a question and answer session, direct practice in using AI technology such as Chat GPT, Microsoft Bing, and the GoDentist application, and a post-test to measure understanding after socialization. The results showed that the average pre-test score of the 13 children was 56.15, while the average post-test score increased to 70, indicating a significant increase in the children's understanding and skills. Although some children showed no change or experienced a decline in their grades, overall, the learning process was successful in improving children's abilities. These results demonstrate the effectiveness of the learning methods used, although further evaluation is needed to address declines in grades in some children and ensure optimal progress for all participants.